Interleukin-10 Promotes Porcine Circovirus Type 2 Persistent Infection in Mice and Aggravates the Tissue Lesions by Suppression of T Cell Infiltration - Du, Qian; Zhang, Huan; He, Mingrui; Zhao, Xuan; He, Jia; Cui, Beibei; Yang, Xuefeng; Tong, Dewen; Huang, Yong (Frontiers in Microbiology, 2019)
Interleukin (IL)-10, as a key anti-inflammatory cytokine, increases during porcine circovirus type 2 (PCV2) infection, but the role of IL-10 in the process remain to be defined. In present study, using an IL-10 deficience mice model, we found that IL-10 deficiency prevented the reduction of splenic lymphocytes (CD45+ cells) induced by PCV2 and promoted CD4+ and CD8+ T cells infiltration in lungs through inducting more T cell chemokines (CCL3, CXCL9, and CXCL10). Simultaneously, PCV2 infection induced a significant increase of pro-inflammatory cytokines and PCV2-specific antibodies in IL-10 deficient mice than that in wild-type mice, resulting in a lower viral load in lung and a milder lung lesion in IL-10 deficient mice relative to wild-type mice. Moreover, the amount of pulmonary CD4+ and CD8+ T cells were all inversely correlated with the lung lesions, as well as the viral load of PCV2. These results demonstrate that PCV2 infection employs IL-10 to block the transfer of T cells to lung of mice, and the IL-10 attenuates the production of pro-inflammatory cytokines and PCV2-specific antibodies. The lack of T cells infiltration, pro-inflammatory cytokines and PCV2-specific antibodies promote PCV2 replication, leading to a more severe lung lesion in mice.